Development of Android Application-Based E-Learning Learning Media Using the Borg and Gall Method - Jamaludin, Dieng Asep; Henderi, Henderi; Bin Ladjamudin, Al Bahra (JINAV: Journal of Information and Visualization, 2024)
The problems of this study are twofold. Namely, the need for the development of learning media with a student-centered learning model (Student Centered Learning), because the traditional learning process is inefficient and very difficult to apply to current training participants. The research method is needs analysis, using an industry-based development model (Borg and Gall) where research findings are used to design learning products, which are then systematically tested in the field, so that specific products can be produced and the effectiveness of the product can be tested. The results of the validator evaluation for e-learning learning media are 79.00% which can be interpreted as quite effective to use; for the evaluation of the benefits of e-learning learning media as learning materials, the results obtained are (1) 81.00 The results of the practicality test evaluation from the display aspect are 86.08% which can be interpreted as practical to use. The results of the effectiveness test evaluation from aspects (1) 87.77% and (2) 87.38% can be interpreted as Very Good to Use, because the effectiveness value of e-learning learning media as a learning resource is 87.60%. The development of e-learning media has become a major focus in schools, especially in SMK Negeri 7 Kota Serang, which is a learning aid that is in accordance with the learning needs of the school. Therefore, a well-structured e-learning media was created.it can be seen on correlation result where factor Education facility has the highest negative correlation value is -0.526.